Determinan Kejadian Stroke Iskemik Pasien Rawat Inap di RSUD Petala Bumi Provinsi Riau Tahun 2019 - Aditya Prayoga; Zulmeliza Rasyid (STIKes Hang Tuah Pekanbaru, 2022)
An ischemic stroke is an event of blockage of blood flow to the brain which stops due to atherosclerosis or a blood clot that blocks a blood vessel. In ischemic stroke, blockage occurs along the arteries leading to the brain. The research objective was to determine the risk factors for the incidence of ischemic stroke inpatients ward at Petala Bumi Hospital, Riau Province in 2019. This type of research was quantitative observational analytic with a case-control design. Location This research was conducted at Petala Bumi Hospital, Riau Province by reviewing medical record data in July-August 2020. The sample of this study consisted of 70 cases and 70 controls. The sampling technique used is Quota Sampling. Data analysis methods include univariate and bivariate analysis, using the chi-square test. The results of the bivariate analysis showed that the variables associated with the incidence of ischemic stroke were blood pressure p-value = 0.002 (OR = 3.052 CI 95% 1,532-6,082), blood sugar p-value = 0.017 (OR = 2.411 CI 95% 1,218-4,772), total cholesterol p-value = 0.007 (OR = 2,700 95% CI 1,363-5,350) and obesity p-value = 0.017 (OR = 2.427 95% CI 1,223-4,816). It is advisable for officers/doctors to provide information about a healthy lifestyle such as regulating diet and adequate physical activity regularly.